Pengaruh Political Visibility, Profitabilitas, Dan Leverage Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (Studi Empiris Pada Industri Pertambangan Yang Terdaftar Di Bei Tahun 2016-2018) - Salma Karina Seputra; Fitra Dharma; Pigo Nauli; Lindrianasari Lindrianasari (Universitas Bandar Lampung (UBL), 2022)
The purpose of this study was to analyze the effect of company size and number of employees proxies for Political Visibility, Return on Assets (ROA) intermediaries for Profitability, Debt to Equity Ratio (DER) intermediaries for Leverage on Corporate Social Responsibility (CSR) exposures. The thing in this review is a mining organization recorded on the Indonesia Stock Exchange (IDX) in 2016-2018. The example in this study was taken involving purposive examining strategy to acquire an example of 29 organizations. Information examination utilizing numerous direct relapse investigation strategy with the assistance of the IBM SPSS Statistics 20 program. The outcomes showed that organization size and benefit factors genuinely huge beneficial outcome on corporate social obligation revelation, while the number of employees and leverage variables statistically had no positive and insignificant effect. on the disclosure of corporate social responsibility.